Pengaruh Produktivitas Kerja Karyawan terhadap Kinerja Perusahaan: Studi Kasus pada Online Shop WNJ.ID - Nisa, Najwa Kamilatun; Puspita Dewi, Lies Anggi (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024)DO - 10.51211/jak.v12i1.2821, 2024)
The purpose to be achieved in this study is to determine the effect of employee work productivity on the performance of the online shop company “WNJ.ID”, to find out how much influence employee work productivity has on company performance and to find out whether company performance can be measured from the work productivity of its employees. Based on the results, the simple regression line equation is as follows Y = 4.150 + 0.891 (X) + e. Based on the results of the coefficient of determination test, the R Square value is 0.754, which means that the company performance variable (Y) can be explained by the work productivity variable (X) by 75.4%, while the remaining 25.6% is explained by other variables outside the model studied. The results of this study indicate that the work productivity variable has a positive and significant effect on company performance with a statistical t value of 10.054 and a significant value of 0.000 which is smaller than the significant value of 0.05. This indicates that the higher the level of work productivity, the higher the level of productivity. This shows that the higher the level of work productivity, the more the value of company performance increases, and vice versa. The contribution of this research is as decision support WNJ.ID can meet expectations, be able to increase work productivity, and can motivate staff to work harder to further improve business performance.     Keywords: work productivity, company performance, productivity, work, performance.